Achieving Higher-Fidelity Conjunction Analyses Using Cryptography to Improve Information Sharing - Hemenway, Brett (RAND Corporation, 2014)
This report examines the feasibility of using modern cryptographic tools to improve space situational awareness. Specifically, the authors examine the applicability of secure multiparty computation (MPC) protocols as a means to compute the collision probability of two satellites. MPC protocols would provide satellite operators with a way to compute such "conjunction analyses" while maintaining the privacy of each operator's orbital information.